The Benefits and Barriers, and Health Behaviors toward Preventing the Spread of Coronavirus in Elderly - Trairatnopas, Veeranuch (Journal of The Royal Thai Army Nurses, 2021)
This research is correlation descriptive research with objectives were to study the relationship between perceived benefits and perceived barriers, and health behaviors toward preventing the spread of Coronavirus in elderly. The sample was 330 elderly people, by using simple random sampling. Data were collected through questionnaires, which had reliability by Conbrach’s alpha coefficient of questionnaire; questionnaire on perception of the benefits, questionnaire on perception of the barriers, and questionnaire on health behaviors toward preventing the spread of Coronavirus in the elderly was 0.904, 0.797, and 0.804 respectively. The data were analyzed by using statistic descriptive and statistically analyzed for the relationship with Pearson’s correlation coefficient. The results of this research were as follows: Perception of the benefits toward preventing the spread of Coronavirus. Overall, it was at a good level. Perception of the barriers toward preventing the spread of Coronavirus. Overall, it was at a good level. The health behaviors toward preventing the spread of Coronavirus. Overall, it was at a good level. The perception of the benefits toward preventing the spread of Coronavirus was a positive significantly correlated with the health behaviors toward preventing the spread of Coronavirus with statistically significant at the .01 level and the perception of the barriers toward preventing the spread of Coronavirus was a negative significantly correlated with the health behaviors toward preventing the spread of Coronavirus with statistically significant at the .01 level. The results of this study suggest the guideline to improve the service and ability for ensuring the readiness go on to control for preventing the spread of Coronavirus.